Orthographic Processing of Spanish as a Heritage Language in Gibraltar: The Role of Interactional Context in Interference Control - Alicia Mariscal (Languages)
Despite the increase in studies on Spanish as a heritage language (SHL), few focus on spelling, with research limited to the U.S. According to the adaptive control hypothesis, language production is governed by control processes, which adapt to the demands of real-world interactional contexts. In this article, these control processes are inferred from the interlingual spelling errors observed in Gibraltarian SHL speakers. The hypothesis is that the Gibraltar dense code-switching context will be manifested in a high number of interlingual misspellings in Spanish due to English interference. Misspellings were identified in the written productions of a sample of 80 Gibraltarian pre-college SHL students (N = 40 in Spanish; N = 40 in English), collected via availability tests and stored in the Dispolex dataset by the members of the project “Lenguas en contacto y disponibilidad léxica: la situación lingüística e intercultural de Ceuta y Gibraltar”. Gibraltarians’ Spanish misspellings were then compared with those found in the U.S. The high percentage of spelling errors in SHL students in Gibraltar might be explained in light of lower inhibitory control of interferences in dense code-switching interactional contexts.